ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM DI SEKOLAH SMP MUHAMMADIYAH 6 JAKARTA - Hafiz, M; Suherdi, Didi (Jurnal Tarbiyah Jamiat Kheir, 2025)
The competence of school principals is at stake in this era, covering holistically various areas of life so that there are no longer visible concrete binding boundaries, as a result a good filter is needed. This research aims to analyze the strategic role of school principal leadership in improving the quality of Islamic Religious Education (PAI) at SMP Muhammadiyah 6 Jakarta. Using a qualitative approach through case studies, this research collected data through in-depth interviews with school principals, PAI teachers, and students, learning observations, and analysis of school documents. Research findings show that school principals apply a transformational leadership model with a focus on three main aspects: (1) developing the professionalism of PAI teachers through training programs and academic supervision, (2) integrating Al-Islam and Muhammadiyah (AIK) values ​​in all school activities, and (3) learning innovation through the use of digital technology. The results can be seen in improving the quality of the PAI learning process and strengthening students' religious character. The obstacles faced include disparities in students' religious understanding and limited learning support facilities. This research concludes that the effectiveness of the principal's leadership in improving the quality of PAI is very dependent on the consistency of program implementation, support from all stakeholders, and the development of a conducive school environment. Research recommendations include strengthening collaboration with parents and optimizing the use of school resources.